Enhanced Auditors Performance Through the Consequences of Management Control System - Adanan Silaban (Indonesian Journal of Business Analytics, 2024)
It is believed that Management Control System (MCS) is world-wide suggested as prerequisite key drivers on any performance to enable to make congruent decision based on holistic monitoring, focusing approach, legitimating-based as well as strategic decision making. Current study aims at investigating the impact of MCS on enhanced auditor’s performance mediated by audit and budgetary control capability. Deployed Structural Equation Modeling with AMOS to analyze data. A survey with questionnaires and Google forms method were used to collect data from 200 auditors with a non-purposive sampling technique. The statistical outputs demonstrated that the impact of the attention focusing approach and strategic making decision are insignificant on budgetary control capability, while the rest of hypotheses, holistic monitoring-based, work legitimating-based showed the positive and significant impact on audit and budgetary capability, more over the mediating variables also statistically proven as the antecedents of enhanced auditors’ performance.